The Effect of The Active Discussion Strategy on The Achievement of Physiology among First-Year Students at The Medical Technical Institute - Asst.Pprof.Dr. Haider Majed Alhashemi; Asst.prof. Miaad Nathem Rasheed (Journal of Educational and Human Sciences, 2022)
The current study seeks to identify the effect of the active discussion strategy on the achievement of physiology among first-year students at the Medical Technical Institute. With the control group, by dividing the sample into two groups, the first experimental group receives instruction using the active discussion strategy in physiology, and the second is the traditional method in the same subject. After applying the experiment and applying the post-test to it, the study reached the following results:The active discussion strategy has a clear impact on raising the level of students' achievement in physiologyThere is a clear superiority of the experimental group over the control group in post-achievement based on the effect of the strategy used in raising the level of achievement.